Characterizing nanoparticles with a laboratory diffractometer: from small-angle to total X-ray scattering. Issue 1 (10th November 2014) - Sommariva, Marco; Gateshki, Milen; Gertenbach, Jan-André; Bolze, Joerg; König, Uwe; Vasile, Bogdan Ştefan; Surdu, Vasile-Adrian
<x content-type="archive" xml:space="preserve">Abstract</x> X-ray diffraction and scattering on a single multipurpose X-ray platform have been used to probe the structure, composition, and thermal behavior of TiO2 nanoparticles ranging in size from 1 to 10 nm. Ambient and non-ambient Bragg diffraction, small-angle X-ray scattering (SAXS), as well as total scattering and pair-distribution function (PDF) analysis are combined to obtain a comprehensive picture of the samples. At these ultrasmall particle-size dimensions, SAXS and PDF prove powerful in distinguishing the salient features of the materials, in particular the size distribution of the primary particles (SAXS) and the identification of the TiO2 polymorphs (PDF). Structural features determined by X-ray scattering techniques are corroborated by high-resolution transmission electron microscopy. The elemental make-up of the materials has been measured using X-ray fluorescence spectrometry and energy-dispersive X-ray analysis.